Study about the energy expenditure assessment in rhythmic gymnastics - Manos, M.; Grigore, V.; Popescu, L. (Annals of Ovidius University Constanta-Series Physical Education and Sport/Science, movement and health, 2012)
Purpose. Determining the effort functional demands in the rhythmic gymnastics activity, in order to optimize the relation between the training stage requirements and the female athletes` specific individual support; drawing up a model focused on the competitive situation characteristics, starting from the involved energetic processes and the achieved specific technical actions. Methods. The experiment was conducted on a group of 10 female gymnasts, components of the Romanian national squad. The used methods aimed at measuring/ assessing the oxygen consumption and the other physiological indicators, under lab, training and simulated competitive conditions. Results. The obtained results emphasize the following aspects: • the team gymnasts present relatively homogeneous aerobic capacities (VO2 max 52.7 ± 2.29), by having in view their morphological characteristics and their age (15 to 17 years old); • the mean lactate and its peak, registered after 1 minute of effort, confirm the fact that, in competitions, gymnasts work under conditions close to their maximal aerobic power; • the registered lactacidemia highlights the same hierarchy within the team in both of the group events, except for the substitute gymnasts, who are in difficulty to supply the requested effort; • the lactic acid higher concentration explains the important exertion of the lactacyd anaerobic system; •a higher lactacidemia is registered in the group titular gymnasts performing with 2 hoops and 3 ribbons (x =11.31 +/- 1.54 mmol/l) and in the rope individual event (x=11.08 +/- 2.38 mmol/l) as compared to the values obtained in the 5-ball group event (x= 10.33 +/- 1.45 mmol/l). This might result from the requirements imposed by the FIG Code of Points as for the number, the degree of technical difficulties and the corporal group specific to each apparatus. Conclusions. The repeated analysis of the heart rate evolution registered during the training lesson, in different preparatory stages, enabled us to objectively determine the characteristics of the demands and of the supplied effort. To accomplish the top-level technical-artistic content in group events, gymnasts must cope with higher energy expenditure, therefore with a strong exertion of the lactacyd anaerobic system, which can become the source of technical errors and can influence both coordination and emotional balance. To lessen this part of the metabolic process in the energy input needed by the effort sustaining in rhythmic gymnastics, it would be necessary to develop first of all gymnasts` aerobic potential, so that they become able to cope with the training effort, to increase their recovery possibilities and delay the lactic acid production.